2014
DOI: 10.1073/pnas.1414146111
|View full text |Cite
|
Sign up to set email alerts
|

Motive attribution asymmetry for love vs. hate drives intractable conflict

Abstract: Five studies across cultures involving 661 American Democrats and Republicans, 995 Israelis, and 1,266 Palestinians provide previously unidentified evidence of a fundamental bias, what we term the "motive attribution asymmetry," driving seemingly intractable human conflict. These studies show that in political and ethnoreligious intergroup conflict, adversaries tend to attribute their own group's aggression to ingroup love more than outgroup hate and to attribute their outgroup's aggression to outgroup hate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 32 publications
3
91
0
1
Order By: Relevance
“…The protocol was identical to that in Study 3b, with the following exception: We randomly assigned participants to receive (or not receive) an instruction intended to incentivize honest reporting. In the incentivized condition, participants read the following instruction, adapted from Waytz, Young, and Ginges (2014), who showed that it successfully reduced a form of biased perception (i.e., the 'motive attribution asymmetry'): "You will see a series of 5 images, and will be asked questions about each one. The participant whose responses are most accurate across images will receive a $12 bonus on mTurk."…”
Section: Study 4 Methodsmentioning
confidence: 99%
“…The protocol was identical to that in Study 3b, with the following exception: We randomly assigned participants to receive (or not receive) an instruction intended to incentivize honest reporting. In the incentivized condition, participants read the following instruction, adapted from Waytz, Young, and Ginges (2014), who showed that it successfully reduced a form of biased perception (i.e., the 'motive attribution asymmetry'): "You will see a series of 5 images, and will be asked questions about each one. The participant whose responses are most accurate across images will receive a $12 bonus on mTurk."…”
Section: Study 4 Methodsmentioning
confidence: 99%
“…Ingroup love and outgroup hate are distinct constructs (Brewer, 1999;Halevy, Bornstein, & Sagiv, 2008;Waytz, Young, & Ginges, 2014). The separateness provides the encouraging possibility that interventions promoting one do not necessarily harm the other.…”
Section: Future Directionsmentioning
confidence: 99%
“…de Dreu (2010) similarly found that individual differences in pro-social (compared with pro-self) orientation determined self-sacrificing for the benefit of the ingroup, but not penalizing of outgroup members. In other areas, adversarial groups in political or ethno-religious conflict tend to attribute their own group's aggression to ingroup favoritism more so than outgroup hostility, whereas aggression from outgroup members is attributed more to outgroup hostility toward the perceivers' group (Kaiser, Eccleston & Hagiwara, 2008;Waytz, Young & Ginges, 2014). And finally, genetic (Lewis & Bates, 2014), neurological (Baumgartner, Schiller, Rieskamp, Gianotti & Knoch, 2014) and developmental (Buttelman & Böhm, 2014) markers of ingroup favoritism, as distinct from outgroup hostility, have also recently been documented.…”
Section: Favoritism Hostility and Multiculturalismmentioning
confidence: 99%